ELECTROCARDIOGRAPHIC FOLLOW-UP OF PATIENTS RECOVERED FROM COVID-19 INFECTION. A CASECONTROL STUDY IN SULAIMANI CITY - Hamid, Dler Shamsulddin (Journal of Sulaimani Medical College, 2024)
Background Electrocardiography (ECG) is one of the simplest, informative and valuable method to assess cardiac abnormalities associated with different illnesses especially during acute viral infections. The role of ECG was confirmed during previous pandemics in identifying various cardiac abnormalities. During covid-19 pandemic cardiac problems was of special concern, it appeared as second cause of mortality and morbidity after respiratory system complications Objectives To identify ECG abnormalities after recovery from mild to moderate SARS-COV-2 infection. Materials and Methods This preliminary case control study was conducted over a period of eight months from February 2021- December 2021 in the Internal Teaching Hospital and private clinic sector in Sulaimani city- Iraq. The study recruited 163 patients recovered from mild to moderate covid-19 disease and was compared to 100 matched control non infected group. Patients with severe covid-19 disease, history of heart failure and those with cardiac electrical conduction diseases were excluded from the study. Following ECG parameters were assessed among studied groups: heart rate (HR), P-R interval, R-R interval, QRS dispersion, corrected QT (QTc) and any sort of ST change. Evidence and types of arrhythmias were taken into account. Results The mean age ± SD (standard deviation) of participants were (48.98 ± 13.7 SD). Regarding gender distribution, ninety-nine (99/163) of the studied cases were female (60.7%) while 64 (64/163) (39.3%) were male. Majority of studied group were cigarette smoker (122/163 vs 41/163) and only 6.1% of them were regular alcohol drinker. The study demonstrated a significantly shorter QRS dispersion among recovered group compared to the control group (15.38 ± 8.29 SD vs 17.94 ± 11.9 SD) with a P- value of 0.04. Additionally, the mean corrected QT interval (QTc) was significantly lower in covid-19 recovered group compared with control group with Pvalue of <0.001 (406.94 vs 440.77). Meanwhile, no statistically significant changes were noted in P-R interval, R-R interval, heart rate, ST segment changes and any kind of arrhythmias between the studied and controlled groups. Conclusion This study concluded that three months after recovery from mild to moderate SARS-COV-2 infection did not demonstrate significant remanent changes compared to non-infected control group.
Keywords: SARSCOV2; Electrocardiography; and Pneumonia